Three new species of Merma Weise (Coleoptera: Coccinellidae: Epilachnini) from Madagascar - Szawaryn, Karol; Czerwinski, Tomasz (Zootaxa, 2023)
The herbivorous ladybird genus Merma Weise was regarded as an African endemite, however, recent examination of the type material of the two Malagasy species Epilachna hovana Sicard,1908 [now Merma hovana (Sicard,1908)] and Peralda quadriguttata Sicard, 1909 [now Merma quadriguttata (Sicard, 1909)], revealed they also belong to that genus. Here further three new species of Merma from Madagascar, M. ankarana sp. nov., M. antakotako sp. nov. and M. fisheri sp. nov., are described, diagnosed and illustrated. An updated key to species of Merma from Madagascar is also provided.